2012
DOI: 10.4049/jimmunol.1004143
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pneumoniaeStimulates a STING- and IFN Regulatory Factor 3-Dependent Type I IFN Production in Macrophages, which Regulates RANTES Production in Macrophages, Cocultured Alveolar Epithelial Cells, and Mouse Lungs

Abstract: Streptococcus pneumoniae is the leading cause of community-acquired pneumonia. In this study, we examine an innate immune recognition pathway that senses pneumococcal infection, triggers type I IFN production, and regulates RANTES production. We found that human and murine alveolar macrophages as well as murine bone marrow macrophages, but not alveolar epithelial cells, produced type I IFNs upon infection with S. pneumoniae. This response was dependent on the pore-forming toxin pneumolysin and appeared to be m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
93
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(101 citation statements)
references
References 61 publications
(66 reference statements)
4
93
3
Order By: Relevance
“…Moreover, in this study, phagocytosis of bacteria by host macrophages was involved in S. pneumoniae-induced IL-1␣ production. We and others previously suggested that S. pneumoniae cells internalized by macrophages underwent rapid death and released PLY, thereby destabilizing phagosomal membranes in a PLY-dependent manner (11,35). Interestingly, phagosomal destabilization by particulate NLRP3 activators has been proposed to facilitate the production of IL-1␣ independently of the inflammasome machinery (30).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in this study, phagocytosis of bacteria by host macrophages was involved in S. pneumoniae-induced IL-1␣ production. We and others previously suggested that S. pneumoniae cells internalized by macrophages underwent rapid death and released PLY, thereby destabilizing phagosomal membranes in a PLY-dependent manner (11,35). Interestingly, phagosomal destabilization by particulate NLRP3 activators has been proposed to facilitate the production of IL-1␣ independently of the inflammasome machinery (30).…”
Section: Discussionmentioning
confidence: 99%
“…Ex vivo human lung tissue and cells were infected with S. pneumoniae D39 wild type [243,244] or S. pneumoniae D39Δply [245], carrying a pneumolysin deletion mutation [246], or S. pneumoniae D39ΔspxB with a deletion of the pyruvate oxidase gen [247]. For in vitro experiments, cells were infected with pneumococci deficient of the capsule (D39Δcps) [248] or double deficient mutants of the capsule and pneumolysin (D39ΔcpsΔply) [245].…”
Section: Bacteriamentioning
confidence: 99%
“…For in vitro experiments, cells were infected with pneumococci deficient of the capsule (D39Δcps) [248] or double deficient mutants of the capsule and pneumolysin (D39ΔcpsΔply) [245].…”
Section: Bacteriamentioning
confidence: 99%
“…Among NOD-like receptors (NLRs), NOD2 recognizes pneumococcal peptidoglycan and NLRP3 is activated by PLY [12][13][14][15]. Moreover, AIM2 as well as another STING-dependent cytosolic DNA sensor detect pneumococcal nucleic acid in the host cell cytosol [7,12]. These receptors primarily regulate the production of NF-κB-dependent proinflammatory mediators, IL-1 family cytokines, and type I IFNs.…”
Section: Introductionmentioning
confidence: 99%
“…Important virulence factors of S. pneumoniae are the exotoxin pneumolysin (PLY) [3], and the polysaccharide capsule that inhibits phagocytosis, complement factor binding, and entrapment by neutrophil extracellular traps [4][5][6]. The innate immune system detects S. pneumoniae through pattern recognition receptors (PRRs) that belong to different protein families and functional classes [7,8]. For example, the Toll-like receptor (TLR) members TLR2 and TLR9 detect pneumococcal cell wall components and CpG-rich DNA, respectively [9][10][11].…”
Section: Introductionmentioning
confidence: 99%